2009
DOI: 10.1254/jphs.09r01cr
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by Vanadium Compounds Targeting Akt-Mediated Signaling

Abstract: Abstract. Treatment with inorganic and organic compounds of vanadium has been shown to exert a wide range of cardioprotective effects in myocardial ischemia/reperfusion-induced injury, myocardial hypertrophy, hypertension, and vascular diseases. Furthermore, administration of vanadium compounds improves cardiac performance and smooth muscle cell contractility and modulates blood pressure in various models of hypertension. Like other vanadium compounds, we documented bis(1-oxy-2-pyridinethiolato) oxovanadium (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 131 publications
(180 reference statements)
2
25
1
2
Order By: Relevance
“…Our results showed that PCA significantly decreased hypoxia/ reoxygenation-induced cardiomyocyte apoptotic rate and the expression of cleaved caspase-3. Akt protein kinase is an important mediator of cardiomyocyte growth and survival (34,35). Previous studies indicated that activation of Akt could suppress apoptosis and promote survival of cardiomyocytes in ischemic heart disease (36).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that PCA significantly decreased hypoxia/ reoxygenation-induced cardiomyocyte apoptotic rate and the expression of cleaved caspase-3. Akt protein kinase is an important mediator of cardiomyocyte growth and survival (34,35). Previous studies indicated that activation of Akt could suppress apoptosis and promote survival of cardiomyocytes in ischemic heart disease (36).…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological beta-AR agonist and blockers are in clinical practice for maintaining the sympathetic drive in cardiovascular diseases [4;29]. The empirical evidences suggest their role in diabetic cardiomyopathy [3]. During heart failure there is remarkable down regulation of beta-AR [4;29].…”
Section: Discussionmentioning
confidence: 99%
“…There are various studies indicating a potential relationship between cardiac hypertrophy, angiogenesis, and cardiac dysfunction, but the mechanisms by which cardiac hypertrophy develops into congestive heart failure are still unclear (7,8,28,29). It has been postulated that for the purpose of maintaining cardiac function, cardiac hypertrophy occurred (1), which led to myocardial hypoxia because of the mismatch between cardiac angiogenesis and the increased size of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%